A cross-sectional study about socio-demographic factors and clinical characteristics of male patients with alcohol dependence syndrome - KARANDIKAR, NEERAJ J; RAUT, PRITISH K; TAGAD, PRASAD K (International Journal of Clinical and Biomedical Research, 2021)
Background: Alcohol abuse is one of the major causes of death and disability globally; and a key risk factor for health, social, and economic problems in the communities. Consumption of alcohol by Indians has increased drastically due to various factors and in an unrestricted manner; and the age of initiation of drinking is progressively coming down. Objective: To determine the socio-demographic and clinical profile of the patients coming for treatment of alcohol dependence syndrome in the psychiatry department. Methods: A cross-sectional study was conducted on 50 male outpatients of alcohol dependence syndrome attending the department of psychiatry at a tertiary care hospital. Sociodemographic data and clinical details were recorded with the help of a pre-designed questionnaire. Results: Nuclear family, family history of alcoholism, unmarried status, higher educational level, unemployment, and peer pressure are the factors significantly associated with early age at first drink and age of dependence on alcohol (p < 0.05). Conclusion: Adolescents having a family history of alcoholism are a high-risk group for developing alcohol dependence and should be targeted for intervention strategies. Community based-longitudinal studies are needed to understand multiple factors influencing alcohol use and recommend targeted preventive measures. Keywords: Alcohol, Alcohol dependence syndrome, Peer pressure, Intoxication, Socio-demographic factors